The Influece of Economics Learning Based on Financial Literacy on High School Students’ Financial Understanding - Hafifah Azzahra Lathifunnisa; Suranto Suranto (Vifada Journal of Education, 2026)
The low level of financial literacy among high school students in Indonesia often triggers a consumptive lifestyle and an inability to manage personal finances. This quantitative research aims to examine the influence of economics learning based on financial literacy on students' financial understanding. The research involved 315 students from SMA Negeri 1 Karanganom for the 2025–2026 academic year, selected thru purposive sampling technique. Data were collected using a Likert scale questionnaire and analyzed using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) model. The results of the hypothesis test show that economics learning based on financial literacy has a positive and significant effect on students' financial understanding, with a sample coefficient of 0.982 and a p-value < 0.05. These findings indicate that the more effective the integration of financial literacy into the curriculum, the broader the students' financial understanding. In conclusion, relevant and contextual economic learning is far more effective than a theoretical approach in helping students manage their finances wisely. Although there are technical limitations related to discriminant validity, these results underscore the importance of innovative educational methods to shape a financially independent younger generation that is ready to face future economic challenges.